(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2025)
A Constitutional Reform to Achieve Peace? The Tension between Constitutional Law and ‘Coercive’ Diplomacy in the Armenia–Azerbaijan Conflict over Nagorno-Karabakh The paper examines the constitutional implications of the agreement signed on August 8, 2025, between Armenia and Azerbaijan, concerning the determination of Nagorno-Karabakh’s status and the normalization of bilateral relations. Among its provisions – though not formally codified – there is a request to revise the Preamble of Armenia’s 1995 Constitution, a condition that has encountered significant domestic resistance. The case is of relevance in the field of comparative constitutional law, as it reflects a growing trend whereby constitutional revision is employed as a strategic instrument of negotiation in the context of international agreements.